Cordyceps spp. as a Sports Supplement and Its Effects on Physical Performance: A Narrative Review - Mularczyk, Karolina Natalia; Łyko, Mateusz; Mszyca, Igor; Kasperczak, Filip; Browarska, Emilia; Miemczyk, Katarzyna; Wołek, Filip Tadeusz; Michalski, Łukasz; Gajewska, Nicole; Kucharski, Kacper; et al. (Quality in Sport, 2026)
Introduction. Today’s sports medicine, physical medicine and rehabilitation are based on metabolism, energy production and use recovery following exertion. Cordyceps species (C. sinensis, C. militaris) rich in cordycepin, adenosine, and polysaccharides, possess unparalleled immunomodulating, anti-oxidant and bioenergetic qualities which make them suitable for athletes as well as individuals suffering from chronic illnesses. Research objective. In this narrative review, we discuss the scientific evidence regarding Cordyceps spp. use as a sports supplement and for therapeutic application in clinical practice with respect to aerobic performance, respiratory- metabolic parameters, fatigue biomarkers and other more general clinical outcomes. Methodology. A systematic search of the PubMed, Scopus, Web of Science and NCBI databases was conducted (January–May 2026). Inclusion criteria were articles in English published from 2020 to 2026. The extracted data were processed by an overall qualitative synthesis. Conclusions. Supplementation with Cordyceps spp. results in greater ergogenic effects through the rightward shifts of ventilatory thresholds, improved SpO2 and enhanced mitochondrial ATP resynthesis. Bioactive compounds exhibit the up-regulation of SOD and catalase activity, reduction in MDA contents, as well as the relief of serum fatigue markers (lactic acid, BUN, CK, LDH). It also accelerates CD34+/Pax7+ stem cells homing to muscle micro-damages for a more rapid reduction of DOMS- it protects against sports anemia. In medical settings, Cordyceps has hypoglycemic, lipid-regulating, renoprotective, anti-cancer, and vasculoprotective effects via TLR4/MyD88/p38 and TLR4/TRAF6/NF-kappaB pathways. Nonetheless, the initiation is impeded by a certain degree of gastrointestinal tolerance, allowing for individual dosage modification and specialized supervision. Future directions should also capitalize on state-of-the-art modern bioengineering and focus on long-term RCTs.